The Synergetic Effect of Light Spectra and Selenium Supplementation on Eruca sativa Mill. Growth and Physiological and Metabolic Responses - Cátia Brito; Sónia Andrade; Helena Ferreira; Carlos Matos; Sandra Martins; José Moutinho-Pereira (Horticulturae, 2024)
Eco-friendly lighting systems, like LED lights, can reduce energy consumption in greenhouse operations, have a long lifespan, and enable precise control over plant growth through spectrum selection. On the other hand, Selenium (Se) is a micronutrient with a beneficial role in plant metabolism and an essential element for human health. In this study, we aim to unravel the effects of LED lighting combined with Se supplementation on the physiological behavior, yield, and quality of arugula (Eruca sativa). Arugula plants were cultivated under controlled conditions using two distinct LED lights: full white spectrum (W) and a mix of 80%/20% of red/blue light (R:B). These plants were then supplemented with three levels of Se: 0 mg Se kg−1 soil [0], 0.3 mg Se kg−1 soil [0.3], and 0.6 mg Se kg−1 soil [0.6]. The results showed that stomatal conductance remained unaffected by the light script. However, the plants exposed to R:B displayed more pronounced signs of photodamage and reduced net photosynthetic rate. Supplementation with Se plays a significant role in mitigating light-induced stress and in improving the antioxidant defense system; this was especially notable in R:B plants. Finally, R:B light decreased the accumulation of aboveground biomass, while no significant impact of Se was noticed on this outcome. Se accumulation exhibited a direct and proportional relationship with the concentration of Se applied. The integration of LED technology and Se supplementation not only enhances crop nutritional value but also aligns with the adoption of more sustainable agricultural practices.